Solar-Wind Hybrid Power Generation System Optimization Using Superconducting Magnetic Energy Storage (SMES) - Nemdili, S.; Ngaru, I. C.; Kerfa, M. (Engineering, Technology & Applied Science Research, 2022)
This paper proposes a renewable energy hybrid power system that is based on photovoltaic (PV) and wind power generation and is equipped with Superconducting Magnetic Energy Storage (SMES). Wind and solar power generation are two of the most promising renewable power generation technologies. They are suitable for hybrid systems because they are environmentally friendly. However, like most renewable energy sources, they are characterized by high variability and discontinuity. They generate a fluctuating output voltage that damages the machines that operate on a stable supply. Therefore, the energy storage system SMES with the function to reduce output voltage fluctuation problems is introduced. SMES is found to be the most effective energy storage device as a result of its quick time response, high power density, and high energy conversion efficiency. In this paper, modeling of a hybrid system with SMES is built using MATLAB/Simulink. Blocks such as the wind model, PV model, and energy storage model are built separately before combining into a complete hybrid system with SMES. Varying wind speed and solar irradiance values are taken as the input parameters. The obtained results from the simulation reveal that a system with SMES is more reliable than a system without SMES.